A holistic methodology for the non-destructive experimental characterization and reliability-based structural assessment of historical steel bridges. (1st November 2022) - Bouzas, O.; Conde, B.; Cabaleiro, M.; Riveiro, B.
Highlights: Heritage steel bridges can be characterized using non-destructive testing techniques. Numerical models can be updated combining sensitivity analysis and optimization algorithms. The Bayesian inference procedures allow updating prior probabilistic models. Probabilistic approaches are adopted to explicitly consider parameters' uncertainty. This holistic methodology allows the structural assessment of historical steel bridges. Abstract: Nowadays, several historical steel structures present damage and an advanced deterioration state induced by human or natural actions, causing fluctuations in geometrical, physical, and mechanical properties that dramatically affect their mechanical behavior. Due to the economic, cultural, and heritage value, these constructions must be comprehensively assessed to verify their current condition state. This work presents a holistic methodology aimed at the non-destructive experimental characterization and reliability-based structural assessment of historical steel bridges. It comprehends from the experimental data acquisition to the finite element model updating and the probabilistic-based structural assessment to obtain the reliability indexes of serviceability and ultimate limit states. Several sources of information are considered in the evaluation process, thus, results are more realistic and accurate and can be used for optimal decision-making related to maintenance and retrofitting actions. The feasibility of the methodology has been tested on O Barqueiro Bridge, an aging riveted bridge located in Galicia, Spain. The study first involved a comprehensive experimental campaign to characterize the bridge effectively at multiple levels: geometry, material, and structural system by the synergetic combination of different tools and methods: in-depth visual inspection, terrestrial laser scanner survey, ultrasonic testing, and ambient vibration test. Subsequently, a detailed FE model was developed and calibrated with an average relative error in frequencies of 2.04% and an average MAC value of 0.94. Finally, the reliability-based structural assessment was performed, yielding reliability indexes of 1.80 and 1.99 for the serviceability and ultimate limit states, respectively. Thus, the bridge could not withstand traffic loads with satisfactory structural performance in its current condition.